Pengembangan UMKM Melalui Pemanfaatan Pemasaran Digital dan Media Sosial Pada Desa Sumberjo, Kecamatan Wonosalam, Kabupaten Jombang, Provinsi Jawa Timur - Wilda Daffania Abidin; Putri Marisna; Adelia Qouli Varadisa; Tegar Satria Adi; Dhian Satria Yudha Kartika (Jurnal Informasi Pengabdian Masyarakat, 2023)
Sumberjo Village as a tourist village which is rich in natural resources, ultimately encourages the formation of various kinds of MSMEs. However, until now, the knowledge of MSMEs regarding the use of social media and digital marketing is still considered lacking. Some MSMEs still apply traditional methods of marketing so that the sales they get are less than optimal. The purpose of community service is to help MSMEs to become more familiar with and understand how digital marketing works as a means of marketing or promotion while at the same time providing counseling about the use of social media as a means of digital marketing. Implementation methods in this activity are interviews and observation, counseling, and mentoring. Communities need to be equipped with the basics and equipped with knowledge of the use of digital marketing so that sales development and increase as well as expectations as an MSME-friendly tourist village can be realized